Optimizing mass rearing and field release of Telenomus remus for effective biological control of Spodoptera litura - De-Rui Han; Guang Zou; Chao-Zhou Liu; Xia Wen; Xiao-Fei Yu; Mao-Fa Yang; Guy Smagghe; Jian-Feng Liu; Chun-Yang Huang (Crop Protection, 2026)

Storm-event nitrate export in a karst hillslope: Flow-path partitioning and hysteresis patterns - Na Feng; Jun Zhang; Fa Wang; Zhiyong Fu; Hongsong Chen (CATENA, 2026)

Green extraction of vanadium pentoxide from industrial solid wastes and its electrochemical calcium storage performance - Hainan Li; Jiaqi Lv; Xi Luo; Zimeng Qu; Feng Liu; Yuehong Zhang; Pengfei Wang; Fa-Nian Shi; Jiyan Liang; Yuhan Wu (Journal of Environmental Chemical Engineering, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Electronic structure modulation of biochar for enhanced micropollutants degradation - Fa Shen; Shi-Yan Guan; Jia-Qian Xu; Xiao-Nan Feng; Fu-Xue Wang; Yifei Sun (Chemical Engineering Journal, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Assessing the impact of wind-wave misalignment on floating offshore wind turbine responses under rapid typhoon wind shifts - Zhitong Lv; Fa Li; Hao Wang; Shitang Ke; Xu Hong; Feng Hu; Tongguang Wang (Engineering Structures, 2026)

Spatiotemporal changes of salt crusts in the Ebinur Lake Basin (2005–2025) using a non-linear spectral unmixing model - Chen-Wei Wang; Xiao-Xiao Zhang; Xiao-Ming Cao; Yi-Ming Feng; Jia-Qiang Lei; Sheng-Yu Li; Jia-Xiu Zou; Jie Zhou; Lian-You Liu; Zi-Fa Wang; Xiao Tang (Journal of Arid Environments, 2026)

Upcycling alumina industrial solid waste into vanadium disulfide anode materials for lithium-ion batteries - Runxin Zhang; Xuesong Li; Yuhan Wu; Feng Liu; Weishan Li; Pengfei Wang; Laishi Li; Fa-Nian Shi; Rui Xu; Yusheng Wu (Resources, Conservation and Recycling, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Host preference and parasitism performance of two Habrobracon hebetor populations on three pyralid hosts: Implications for stored-product biocontrol - Hou-Ding Ou; Zhong-Jiu Xiao; Xun-Feng Peng; Mao-Fa Yang; Xiu-Qin Wang (Journal of Stored Products Research, 2026)

Subsurface stormflow concentration-discharge relationships reveal DOC and nitrate transport mechanisms across land uses in karst hillslopes - Na Feng; Jun Zhang; Fa Wang; Zhiyong Fu; Hongsong Chen (Journal of Hydrology, 2026)

Age–Sex Class Variation in the Activity Budget and Diet of Rhinopithecus bieti in Association with Monthly Temperature - Jacob B. Kraus; Zhi Pang Huang; Yan Pang Li; Liang Wei Cui; Shuang Jin Wang; Jin Fa Li; Feng Liu; Yun Wang; Karen B. Strier; Wen Xiao (International Journal of Primatology, 2026)
The energy and nutrient costs associated with body mass, age, and sex can influence variation in primate behavior and diet. However, comparatively little is known about how these factors affect the behavioral and dietary flexibility of Asian colobines in response to intra-annual climate shifts. We collected data on an isolated population of black-and-white snub-nosed monkeys ( Rhinopithecus bieti ) at Mt. Lasha in the Yunling Provincial Nature Reserve, Yunnan, China, using instantaneous and scan sampling across 32 months between May 2008 and August 2016 to assess the association of temperature on the activity budgets and diets among and within age-sex classes. Adult females spent more time feeding, juveniles spent more time moving and less time resting, and adult males spent less time moving and more time resting than other age-sex classes. We did not detect any significant variation in diet across age-sex classes. This population spent more time feeding and less time moving and resting in colder months than in warmer months; however, we only detected these temperature-related effects within age-sex classes for moving and resting, not feeding. This population also spent more time feeding on lichen during colder months than during warmer months, a finding that cannot be explained by temperature-related dietary shifts within age-sex classes because their diets remained stable throughout the year. Our results suggest that intra-annual variation in temperature may amplify the distinct physiological demands among different age-sex classes, leading to greater shifts in activity patterns than in diet composition.

Low-frequency signal inversion and reconstruction via the spatial structure regularization - Wei-wei Gu; Hao Li; Dong-feng Zhao; Peng-fei Wang; Guo-fa Li (Applied Geophysics, 2026)

Modulation of Different Salinity Conditions on Transcriptional Signature of Metabotropic Serotonin and Dopamine Receptors in Nile Tilapia (Oreochromis niloticus) - Ming-Yuan Wu; Pichayapa Meekuan; Zhuo-Hang Feng; Zheng-Xiang Zhang; Ya-Xin Wang; Yue-Yan Sun; Zhi-Shuai Hou; Zhen-Fa Qin (Fishes, 2026)
As freshwater resources become increasingly limited, exploiting brackish and marine waters for aquaculture is viewed as a promising alternative. Nile tilapia (Oreochromis niloticus), although considered euryhaline, shows relatively restricted tolerance to salinity compared with other tilapia species, making it an ideal model to study adaptive responses to osmotic stress. Serotonin (5-HT) and dopamine (DA) are key modulators of stress responses through their activation of metabotropic G protein-coupled receptors (GPCRs). In this study, we investigated the transcriptional profiles of metabotropic serotonin and dopamine receptors across the brain, intestine, and liver of Nile tilapia reared in different salinity conditions (0 ppt, 16 ppt, 30 ppt). The results showed both dopamine and serotonin metabotropic receptors were duplicated with potential neofunctionalization, contributing to osmoregulatory capacity. Nile tilapia showed altered brain drd1, htr1 and htr7 subtypes in response to salt change. Meanwhile, the drd3 subtype showed pronounced alterations in the intestine and liver under elevated salinity. Notable transcriptional alterations in htr4 subtypes were observed in both brain and liver, suggesting their potential involvement in modulating energy balance and stress adaptation. Correlation network analyses further demonstrated coordinated regulation among receptor paralogues in the brain. These findings provide potential targets, such as ligand analog additives or genetic enhancement, for future functional validation and for improving salinity tolerance in Nile tilapia culture.

Quantifying multi-interface runoff-driven nitrogen loss and its control effects in karst hillslopes - Na Feng; Jun Zhang; Fa Wang; Xiajiao Liu; Wei Zhang; Hongsong Chen (Soil and Tillage Research, 2026)

A novel heterogeneous Mo/Mo2C embedded N, P co-doped carbon nanofiber for C-band broadband and strong microwave absorption - Di Yu; Gui-Mei Shi; Qiang Gao; Fa-Nian Shi; Feng Liu; Xing-Hao Qu (Chemical Engineering Journal, 2025)

New insights into tRNA-derived small RNAs in human digestive diseases - Yong-qiang Liu; Feng Chen; Fa Zhang; Yuan-mei Ye; Yu-jie Su; Ya-tao Liu; Yu-fang Leng (Molecular Biology Reports, 2025)

Water stable isotope evidence reveals the impact of soil thickness on mobile water recharge in Karst Hillslopes, Southwest China - Jun Zhang; Na Feng; Jiajie Li; Fa Wang; Kelin Wang; Hongsong Chen (Science China Earth Sciences, 2025)

Integrated multi-omics analysis uncovers Zearalenone-induced ovarian and intestinal inflammation is mediated by the tumor necrosis factor-α - Fa-Li Zhang; Ai-Ying Li; Ke-Xin Zhu; Kai Zhang; Zhe Tian; Tao Wang; Xin-Hao Zhang; Jian Zang; Xiao-Feng Sun; Wei Shen; Lan Li (Journal of Hazardous Materials, 2025)

Influence of the strain rate on the deformation and failure of rocks with multiscale cracks - Yan-jie Feng; Cheng-zhi Qi; Fa Zhao; Tao Li; An-sen Gao; Xiao-yu Ma (Geomechanics for Energy and the Environment, 2025)

Environmental levels of bis(2-ethylhexyl)-tetrabromophthalate (TBPH) cause thyroid toxicity and early carcinogenic signals in juvenile fish - Xiang-sheng Hong; Liang Yan; Wei Sang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jia-jing Xin; Gao-feng Zhao; Xu-fa Ma; Jin-miao Zha (Environmental Pollution, 2025)

Soil water sources and transport modes based on stable isotope tracing in Northeastern Qinghai-Tibet Plateau - Juan Gui; Youjing Yuan; Zongxing Li; Qi Feng; Fa Du (Journal of Mountain Science, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

8 R -methoxy-9 R -hydroxyl-fumitremorgin C, a new diketopiperazine alkaloid from Haima cold seep-derived fungus Aspergillus fumigatus CYH-5 - Yi-Hao Che; Jun-Feng Wang; Xue-Feng Shi; Wen-Ping Ding; Zhi-Hui Xiao; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Natural Product Research, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Corrigendum to “Maternal Zearalenone exposure impacted ovarian follicle formation and development of suckled offspring” [Sci. Total Environ. 788 (2021) 147792] - Li Kong; Ai-Hong Zhao; Qian-Wen Wang; Yan-Qin Feng; Zi-Hui Yan; Ming-Hao Li; Fa-Li Zhang; Han Wang; Kai-Yu Shen; Ying Liu; Yu-Jiang Sun; Wei Shen; et al. (Science of The Total Environment, 2025)

Corrigendum to “Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis” [J Hazard Mater 468 (2024) 133836] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2025)

60Coγ activation of Cladophora rupestris biomass functional groups and its effect on Pb2+ adsorption - Lu-sheng Zhang; Zhao-wen Liu; Chang-fa Qiu; Xiao-yu Feng; Shi-ying Ma; Qian Yin; De-ju Cao (Environmental Science and Pollution Research, 2024)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Overlapping hotspot tracks and melts from diffuse plume materials in the upper mantle generated intraplate seamount groups in the West Pacific - Xun Wei; Guo-Liang Zhang; Ji Zhang; Xue-Fa Shi; Paterno R. Castillo; Yan Zhang; Wan-Feng Zhang; Yi-Gang Xu; Hong-Yan Li; Hui Zhang (Earth and Planetary Science Letters, 2024)

Study on chemical characterization and sleep-improvement function of Prunella vulgaris L. based on the functional components - Chang Zhou; Yi-fan Hu; Yan Zhang; Cheng-hao Wang; Xue-jing Liao; Fa-feng Cheng; Yan-yan Jiang (Food Research International, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

New diketopiperazine alkaloids from the Haima cold seep-derived fungus Toxicocladosporium sp. CYH-18 - Yi-Hao Che; Jun-Feng Wang; Wen-Ping Ding; Zhi-Hui Xiao; Xue-Feng Shi; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Phytochemistry Letters, 2024)

Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2024)

The remediation potential and kinetics of Pb2+ adsorbed by the organic frameworks of Cladophora rupestris - Lu-sheng Zhang; Xiao-yu Feng; Chang-fa Qiu; Ling-sheng Li; Yu Sun; Xin-yi Tao; Xin-yue Li; Zhao-wen Liu; De-ju Cao (Environmental Science and Pollution Research, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Temporal and spatial variations of multivariate hot, dry and windy climate extremes in Northwest China - Yao Feng; Fubao Sun; Fa Liu (International Journal of Climatology, 2023)
The simultaneous occurrence of extreme weather events such as high temperature, low humidity and strong wind speed can cause devastating impacts on the fragile environment and vulnerable ecosystem in arid Northwest China (NW). However, few studies investigate the multivariate compound hot, dry and windy extremes in NW. In this study, we investigate the temporal and spatial variations of the warm‐season trivariate hot, dry and windy (HDW) and bivariate hot and dry (HD), dry and windy (DW), hot and windy (HW) extremes in NW. From 1960 to 2019, we observed more compound HD, DW, HW and HDW days in the hyper‐arid Xinjiang and west Gansu in NW. Simultaneously, DW days, HW days and HDW days consistently declined at rates of −0.48, −0.88 and −0.42 day·10a −1 , except for a discernible increasing rate of 0.56 day·10a −1 in HD days. Notably, trends in four multivariate compound extremes all experienced pronounced reversals from a declining to increasing trend in the 1990s. The higher probability of compound HD, DW and HW extremes contributed to a higher probability of HDW in Xinjiang province. Ultimately driven by the significantly rising temperature (0.21°C·10a −1 , p

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Recent warm-season dryness/wetness dominated by hot-dry wind in Northern China - Yao Feng; Fubao Sun; Hong Wang; Fa Liu (Journal of Hydrology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

One new furanone analogue from the deep-sea fungus Purpureocillium sp. SCSIO 06693 - Ying-Ying Song; Meng-Meng Song; Wei-Hao Chen; Xiao-Yan Pang; Fa-Zuo Wang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2023)

Multifaceted characteristics of summer heat and affected population across China under climate change - Yao Feng; Wenbin Liu; Hong Wang; Fa Liu; Fubao Sun (Climate Dynamics, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

A new critical strain energy release rate failure criterion for anisotropic rock under high confining pressure - Zefan Wang; Chengzhi Qi; Fa Zhao; Kuan Jiang; Yanjie Feng (Geomechanics for Energy and the Environment, 2023)

An integrated strategy combining network toxicology and feature-based molecular networking for exploring hepatotoxic constituents and mechanism of Epimedii Folium-induced hepatotoxicity in vitro - Zhen Zhao; Jin-Fa Du; Qiao-Lei Wang; Fang-Ning Qiu; Xu-Yan Chen; Feng-Jie Liu; Ping Li; Yan Jiang; Hui-Jun Li (Food and Chemical Toxicology, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Leaching characteristics and pollution risk assessment of potentially harmful elements from coal gangue exposed to weathering for different periods of time - Long-qing Shi; Jin-feng Peng; Dong-jing Xu; Jin-jin Tian; Tian-hao Liu; Bin-bin Jiang; Fa-cai Zhang (Environmental Science and Pollution Research, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Indole diketopiperazine alkaloids and aromatic polyketides from the Antarctic fungus Penicillium sp. SCSIO 05705 - Yi-Wei Hu; Wei-Hao Chen; Meng-Meng Song; Xiao-Yan Pang; Xin-Peng Tian; Fa-Zuo Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Genome editing of Corynebacterium glutamicum mediated with Cpf1 plus Ku/LigD - Fa-Yu Yang; Nan Wei; Zhi-Hao Zhang; Mi Wang; Ying-Chun Liu; Li-Fang Zhang; Feng Gu (Biotechnology Letters, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Experimental study on the suffusion mechanism of gap-graded soils under an exceedance hydraulic gradient - Liang Chen; Yu Wan; Jian-Jian He; Chun-Mu Luo; Shu-Fa Yan; Xian-Feng He (Natural Hazards, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Seismic stress perturbation and triggering patterns induced by the 2016 Central Italy earthquake sequences - Lu-peng Zhang; Ding-fa Huang; Zhong-shan Jiang; Wei Feng; Abubakr Hassan (Journal of Mountain Science, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Recycling of subducted Indian continental crust and its significance on post-collisional ultrapotassic magmatism in southwestern Tibet - Izhar Sadiq; Fa-Bin Pan; Hong-Fei Zhang; Chun-Feng Li; Biji Luo; Mohammad Arif (Contributions to Mineralogy and Petrology, 2021)

Short-term streamflow time series prediction model by machine learning tool based on data preprocessing technique and swarm intelligence algorithm - Wen-Jing Niu; Zhong-Kai Feng; Wen-Fa Yang; Jun Zhang (Hydrological Sciences Journal, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Three-dimensional identification of hydrological drought and multivariate drought risk probability assessment in the Luanhe River basin, China - Xu Chen; Fa-wen Li; Jian-zhu Li; Ping Feng (Theoretical and Applied Climatology, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Effects of seasonal water-level fluctuation on soil pore structure in the Three Gorges Reservoir, China - Shu-juan Zhang; Qiang Tang; Yu-hai Bao; Xiu-bin He; Feng-xia Tian; Fa-you Lü; Ming-feng Wang; Raheel Anjum (Journal of Mountain Science, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

The effects of rainfall regimes and terracing on runoff and erosion in the Three Gorges area, China - Qin-xue Xu; Pan Wu; Jun-feng Dai; Tian-wei Wang; Zhao-xia Li; Chong-fa Cai; Zhi-hua Shi (Environmental Science and Pollution Research, 2018)

Spatiotemporal variation of hydrological drought based on the Optimal Standardized Streamflow Index in Luanhe River basin, China - Xu Chen; Fa-wen Li; Ping Feng (Natural Hazards, 2018)

Comprehensive risk assessment and source identification of selected heavy metals (Cu, Cd, Pb, Zn, Hg, As) in tidal saltmarsh sediments of Shuangtai Estuary, China - Chang-Fa Liu; Bing Li; Yi-Ting Wang; Yuan Liu; Heng-Jiang Cai; Hai-Feng Wei; Jia-Wen Wu; Jin Li (Environmental Monitoring and Assessment, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Four new glycosides from the stems of Dendrobium fimbriatum Hook - Feng-Qing Xu; Wei-Wei Fan; Cheng-Ting Zi; Fa-Wu Dong; Dan Yang; Jun Zhou; Jiang-Miao Hu (Natural Product Research, 2017)

Sr-Nd-Pb isotopic compositions of the lower crust beneath northern Tarim: insights from igneous rocks in the Kuluketage area, NW China - Yan Zhang; Xun Wei; Yi-Gang Xu; Xiao-Ping Long; Xue-Fa Shi; Jian-Xin Zhao; Yue-Xing Feng (Mineralogy and Petrology, 2017)

Comparison of immune responses to attenuated rabies virus and street virus in mouse brain - Fa-ming Miao; Shou-feng Zhang; Shu-chao Wang; Ye Liu; Fei Zhang; Rong-liang Hu (Archives of Virology, 2017)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

Emergy assessment of three home courtyard agriculture production systems in Tibet Autonomous Region, China - Fa-chun Guan; Zhi-peng Sha; Yu-yang Zhang; Jun-feng Wang; Chao Wang (Journal of Zhejiang University-SCIENCE B, 2016)

Climate–growth relationship stability of Picea crassifolia on an elevation gradient, Qilian Mountain, Northwest China - Jing-pin Lei; Xiao-hui Feng; Zheng Shi; Deng-zhong Bai; Wen-fa Xiao (Journal of Mountain Science, 2016)

Recursive impedance inversion of ground-penetrating radar data in stochastic media - Zhao-Fa Zeng; Xiong Chen; Jing Li; Ling-Na Chen; Qi Lu; Feng-Shan Liu (Applied Geophysics, 2015)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Tree‐ring reconstruction of July–May precipitation ( AD 1816–2010) in the northwestern marginal zone of the East Asian summer monsoon reveals the monsoon‐related climate signals - Feng Chen; Huiqin Wang; Fa‐hu Chen; Yujiang Yuan; Rui‐bo Zhang (International Journal of Climatology, 2015)
A July–May precipitation reconstruction for the period AD 1816–2010 was developed from a tree‐ring width chronology of Picea wilsonii for the Xinglong Mountains area of Lanzhou. The reconstruction explains 55.8% of the actual precipitation variance during the calibration period from 1951 to 2010. Wet conditions prevailed during the periods 1822–1835, 1843–1858, 1870–1877, 1884–1891, 1911–1921, 1933–1938, 1944–1979 and 2009–2010. Dry episodes occurred during 1816–1821, 1836–1842, 1859–1869, 1878–1883, 1892–1910, 1922–1932, 1939–1943 and 1980–2008. Multi‐taper method spectral analysis indicates the existence of some significant peaks at 2.8, 3.0 and 3.5 years. Spatial correlations with gridded land surface precipitation data revealed that our reconstruction represents regional precipitation signal for a large area of North China linked to the East Asian summer monsoon (EASM). Comparison with other tree‐ring‐based precipitation/drought reconstructions from surrounding areas implies a high degree of confidence for our reconstruction. Precipitation variations in the study area are significantly correlated with sea surface temperatures in eastern equatorial Pacific Ocean and tropical western Pacific Ocean, suggesting a possible connection of regional precipitation variations to the EASM and the El Niño‐Southern Oscillation (ENSO).

Alpha-Synuclein Oligomerization in Manganese-Induced Nerve Cell Injury in Brain Slices: A Role of NO-Mediated S-Nitrosylation of Protein Disulfide Isomerase - Bin Xu; Cui-Hong Jin; Yu Deng; Wei Liu; Tian-Yao Yang; Shu Feng; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Non-alcoholic fatty liver disease and risk of in-stent restenosis after bare metal stenting in native coronary arteries - Ke-Qing Shi; Fa-Ling Wu; Wen-Yue Liu; Chen-Chen Zhao; Chang-Xi Chen; Yao-Yao Xie; Sheng-Jie Wu; Xian-Feng Lin; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Fibroblast proliferation alters cardiac excitation conduction and contraction: a computational study - He-qing Zhan; Ling Xia; Guo-fa Shou; Yun-liang Zang; Feng Liu; Stuart Crozier (Journal of Zhejiang University-SCIENCE B, 2014)

Alpha-Synuclein is Involved in Manganese-Induced ER Stress via PERK Signal Pathway in Organotypic Brain Slice Cultures - Bin Xu; Fei Wang; Sheng-Wen Wu; Yu Deng; Wei Liu; Shu Feng; Tian-Yao Yang; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Distribution and phenotypic expression of mineralocorticoid receptor and CYP11B2 T-344C polymorphisms in a Taiwanese hypertensive population - Sung-Kien Sia; Hui-Ling Chiou; Shiuan-Chih Chen; Chin-Feng Tsai; Shun-Fa Yang; Kwo-Chang Ueng (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Toxicity of CdTe QDs with different sizes targeted to HSA investigated by two electrochemical methods - Zi-Qiang Xu; Lu Lai; Dong-Wei Li; Ran Li; Chen Xiang; Feng-Lei Jiang; Shao-Fa Sun; Yi Liu (Molecular Biology Reports, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

miR-210 activates notch signaling pathway in angiogenesis induced by cerebral ischemia - Yuan-Lei Lou; Fei Guo; Fen Liu; Fa-Liang Gao; Peng-Qi Zhang; Xin Niu; Shang-Chun Guo; Jun-Hui Yin; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2012)

Simulation of biatrial conduction via different pathways during sinus rhythm with a detailed human atrial model - Dong-dong Deng; Ying-lan Gong; Guo-fa Shou; Pei-feng Jiao; Heng-gui Zhang; Xue-song Ye; Ling Xia (Journal of Zhejiang University-SCIENCE B, 2012)

Assessment of economic losses from tropical cyclone disasters based on PCA-BP - Wei-ping Lou; Hai-yan Chen; Xin-fa Qiu; Qi-yi Tang; Feng Zheng (Natural Hazards, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

A checklist of parasitic nematodes from marine fishes of China - Wen-feng Peng; Sheng-fa Liu; Bing-li Wang; Mei-mei Wei (Systematic Parasitology, 2011)

Electrophysiological properties of spinal wide dynamic range neurons in neuropathic pain rats following spinal nerve ligation - Feng-Yu Liu; Xiao-Xiu Qu; Jie Cai; Fa-Tian Wang; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2011)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Detection of nitrogen-overfertilized rice plants with leaf positional difference in hyperspectral vegetation index - Qi-fa Zhou; Zhan-yu Liu; Jing-feng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Digenean parasites of Chinese marine fishes: a list of species, hosts and geographical distribution - Sheng-fa Liu; Wen-feng Peng; Peng Gao; Ming-jun Fu; Han-zhou Wu; Ming-ke Lu; Ji-qing Gao; Jun Xiao (Systematic Parasitology, 2010)

Meiosis and pollen germinability in small-flowered anemone type chrysanthemum cultivars - Fa-Di Chen; Feng-Tong Li; Su-Mei Chen; Zhi-Yong Guan; Wei-Min Fang (Plant Systematics and Evolution, 2009)

Optimal waveband identification for estimation of leaf area index of paddy rice - Fu-min Wang; Jing-feng Huang; Qi-fa Zhou; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Transgenic Bacillus thuringiensis (Bt) cotton (Gossypium hirsutum) allomone response to cotton aphid, Aphis gossypii, in a closed-dynamics CO2 chamber (CDCC) - Gang Wu; Fa Jun Chen; Feng Ge; Yu-Cheng Sun (Journal of Plant Research, 2007)

High-Altitude Windborne Transport of Helicoverpa armigera (Lepidoptera: Noctuidae) in Mid-Summer in Northern China - Hong-Qiang Feng; Kong-Ming Wu; Yun-Xia Ni; Deng-Fa Cheng; Yu-Yuan Guo (Journal of Insect Behavior, 2005)